The Existence of Otanaha Fort in Gorontalo as a Cultural Heritage and Tourist Attraction - Melissa Wala; Hamka Naping; Tasrifin Tahara (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
In this chapter, the research aims to discover Otanaha Fort's existence in the current context. The research uses a qualitative-phenomenological approach, carried out in Dembe I Village, Gorontalo (July-December 2024), and data is collected through observation, interviews, FGDs, and tourist surveys—a total of 16 informants. The results of the study showed. That Otanaha Fort is recognized as a cultural heritage through national and regional regulations, including Law No. 11 of 2010. However, threats such as physical degradation and weak legal sanctions remain challenges. This fort has an important role in the identity of the Gorontalo people, reflected in the oral tradition and the tourism sector. Although the number of tourists has increased, their contribution to PAD has decreased. Revitalization efforts have been made, but less attention has been paid to historical conservation. The main obstacles include coordination between agencies, limited accessibility, and inadequate tourist facilities. Infrastructure improvements, strategic promotions, and sustainable conservation are needed to increase the attractiveness of Otanaha Fort.